2018
DOI: 10.1159/000492278
|View full text |Cite
|
Sign up to set email alerts
|

Prodigiosin Inhibits Proliferation, Migration, and Invasion of Nasopharyngeal Cancer Cells

Abstract: Background/Aims: Nasopharyngeal carcinoma remains a devastating and difficult disease to treat. This study explores the antineoplastic effect of prodigiosin on nasopharyngeal cancer cells. Methods: Human nasopharyngeal carcinoma CNE2 cells and human normal nasopharyngeal epithelial NP69 cells were obtained and treated with prodigiosin or fluorouracil (5-FU). Colony formation assay was performed to screen for the optimal experimental concentrations of prodigiosin and 5-FU, and MTT assay was used to examine cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
(15 reference statements)
2
12
0
3
Order By: Relevance
“…In opposite, the viability of nonmalignant cells (HSF) did not change in all experimental variants. Considering the fact that prodigiosin can suppress cell proliferation, it is expected that the sensitivity of cancer cells to the inhibitory activity of prodigiosin depends on cell proliferation rates (Liu et al, 2018;Sam and Ghoreishi, 2018;Ji et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In opposite, the viability of nonmalignant cells (HSF) did not change in all experimental variants. Considering the fact that prodigiosin can suppress cell proliferation, it is expected that the sensitivity of cancer cells to the inhibitory activity of prodigiosin depends on cell proliferation rates (Liu et al, 2018;Sam and Ghoreishi, 2018;Ji et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have characterized cell migration and proliferation in the progression of tumorigenesis. [12][13][14][15] We showed previously that purified β 2 -GPI inhibits cell migration, proliferation, and angiogenesis in human aortic endothelial cells. [9][10][11] However, the role of natural β 2 -GPI in tumor development remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] It is well established that abnormal cell migration and proliferation are closely related to carcinogenesis. [12][13][14][15] Furthermore, many studies have reported that inhibition of cell migration decreases tumor growth in multiple cancers. [16][17][18] Therefore, it is important to elucidate the cellular basis and molecular mechanisms of β 2 -GPI function in antitumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the anticancer potential of PG and other prodigiosins has been demonstrated through various modes of action, such as apoptosis [34], autophagy [15], cell cycle arrest [14], mitochondrial uncoupling [35], and migration inhibition [36], toxicity studies of PG are not readily available in the literature. The nematode Caenorhabditis elegans is a model system with well-known developmental stages [37] that can be utilized in anticancer drug discovery for toxicity, immunity, and pharmacogenetics studies, among others [38], so it represents a fitting model system for PG toxicity and safety research.…”
Section: Introductionmentioning
confidence: 99%